Biochar research advancement in Bangladesh: challenges and opportunities of biochar in improving soil health - Baquy, M. Abdulaha-Al; Mamun, M. Abdullah Al; Mia, Shamim; Alam, Md. Mahedy; Khan, M. Shahadat Hossain; Rahman, Shah Moinur (Universitas Sebelas Maret, 2022)
Globally, biochar research and its application for soil improvement have attracted the interest of many researchers, primarily environmental and soil scientists, in the last decade. But, a limited number of biochar research studies have been conducted in Bangladesh. Therefore, a comprehensive study on biochar research is necessary to find out the scope and opportunities of biochar application in the soils of Bangladesh. Generally, biochar can improve the physical, chemical, and biological properties of soils. It also has a significant role in greenhouse gas emissions. The contaminated soils can also be remediated through the judicious application of biochar. In Bangladesh, biochar application enhanced soil pH, organic matter, phosphorus availability, and agricultural production while decreasing soil acidification, microbial activity, and heavy metals mobility. Besides that, there were both positive and negative findings regarding nitrogen availability, greenhouse gas emissions, and heavy metal accumulation. However, this review includes the selection of feedstock, the advancement of pyrolysis technology, the characterization of biochar, and the agronomic and environmental benefits of biochar use. This paper also reviews biochar study and application activities in Bangladesh over the last decade. Further research directions have been suggested to ensure the beneficial and safe application of biochar to agricultural property.